ANALISIS PENGARUH ECONOMIC VALUE ADDED, RETURN ON ASSETS, RETURN ON EQUITY, DAN EARNING PER SHARE TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005-2007 - Christine Christine (Universitas Bunda Mulia, 2017)
This research attempted to analyze the leverage between EVA, ROA, ROE, EPS with stock return of the 12 sample companies. The 12 sample companies are the companies that included in LQ-45 at the Indonesia Stock Exchange within period of 2005 to 2007. First, this research computes the score of EVA, ROA, ROE, EPS from each of the companies. To analyze the leverage using linear regression method with stock return as a dependent variable and EVA, ROA, ROE, EPS each as a independent variable. And then comparing the results from the linear regression which method has the greater number of R Square. Also using regression method with stock return as a dependent variable and EVA, ROA, ROE, EPS together as independent variable, then analyzing the results from the regression such as multi collinierity, autocorellation, heteroscedasticity, and normality. Key Words: Economic Value Added (EVA), Return on Asset (ROA), Return on Equity (ROE), Earnings pro Share (EPS), LQ-45 Stock Index.